I only have eyes for you: Oxytocin administration supports romantic attachment formation through diminished interest in close others and strangers. (December 2021) - Freeman, Harry; Scholl, Jamie L.; AnisAbdellatif, Musheera; Gnimpieba, Etienne; Forster, Gina L.; Jacob, Suma
Abstract: Animal studies confirm oxytocin's (OT) role in regulating monogamous sexual behavior in pair-bonding rodents; and human studies are beginning to translate how this highly conserved neuropeptide is implicated in romantic attachment formation. A number of studies have shown how OT promotes relationship exclusivity by diminishing interest in strangers and increasing reward response to partners. Less clear is whether these effects are modulated by romantic duration or life history factors, or if OT's social distancing effects generalize beyond strangers to close relationships. We report the results of a double-blind, placebo-controlled crossover study on the effects of a single dose of intranasal OT (24 IU) on forty-four young adults (91% female) in different stages of romantic attachment formation (M duration=21 months). Participants completed a screening survey and two lab visits separated by 4-weeks, including a diagrammatic measure of attachment to parents and peers, attitudes related to sexual conservatism and partner infidelity, ratings scales of closeness to romantic partners, and visual attractiveness ratings of strangers. Individual differences were examined by life history factors, including maternal love withdrawal and parental separation. Results indicated that OT administration decreased attachment to mothers, decreased attachment to subsidiary attachment figures, and decreased attraction to strangers. In all cases, emotional distancing was stronger among participants in newer romantic relationships. OT increased arousal to partner infidelity and increased sexual conservatism among participants with negative life history experiences (parental separation and high love withdrawal), whereas the reverse was true for participants reporting a more positive life history. Findings suggest that OT supports exclusivity through social distancing from strangers and close others within a sensitive period of attachment formation. In addition, findings indicate OT plays a different role in mate retention strategies by life history. Highlights: Oxytocin decreased stranger attraction, attachment to mothers, and to subsidiary attachment figures. Oxytocin changed sexual attitudes and arousal to partner infidelity. Life history and romantic relationship duration moderated oxytocin effects. Findings indicate a sensitive period for oxytocin's role in attachment formation. Oxytocin did not influence closeness or attraction to romantic partners.